BioEssays 1/2021. (22nd December 2020) - Hojsgaard, Diego; Schartl, Manfred
Abstract : The origins of asexuality in plants as well as animals have long puzzled researchers. In article 2000111, Diego Hojsgaard and Manfred Schartl integrate old ideas with recent molecular and genomic data and provide a single mechanistic model for this phenomenon. They highlight two usually overlooked conditions to understand the molecular nature of clonal organisms to explain asexuals' developmental diversity and biologically vague cases such as automixis and polyploidy.